Synthesis, Characterization, and Thermal and Proton Conductivity Evaluation of 2, 5-Polybenzimidazole Composite Membranes. (29th October 2014) - Lee, Jin-Woo; Kim, Kwangin; Khan, Sher Bahadar; Han, Patrick; Seo, Jongchul; Jang, Wonbong; Han, Haksoo
Abstract : In this contribution, composite membranes (CM-D and CM-S) of 2, 5-polybenzimidazole (PBI) were synthesized by adding inorganic heteropoly acids (IHA-D and IHA-S). IHA-D and IHA-S were synthesized by condensation reaction of silicotungstic acid with tetraethyl orthosilicate (TEOS) in the absence and presence of mesoporous silica (SiO2 ), respectively. The synthesized composites were structurally and morphologically characterized and further investigated the functional relationships between the materials structure and proton conductivity. The proton conductivity as well as thermal stability was found to be higher for composite membranes which suggest that both properties are highly contingent on mesoporous silica. The composite membrane with mesoporous silica shows high thermal properties and proton conductivity. IHA-D shows proton conductivity of almost 1.48 × 10 - 1  Scm −1 while IHA-S exhibited 2 . 0 6 × 10 - 1  Scm −1 in nonhumidity imposing condition (150°C) which is higher than pure PBI. Thus introduction of inorganic heteropoly acid to PBI is functionally preferable as it results in increase of ion conductivity of PBI and can be better candidates for high temperature PEMFC.